KONSEPSI SANKSI ADAT DALAM KASUS PELECEHAN SEKSUAL OLEH OKNUM PEMUKA AGAMA ( STUDI KASUS DI DESA TAMPAKSIRING KABUPATEN GIANYAR ) - Ni Putu Anggie Astriani; Widnyana, I Made Adi Widnyana; Sugita, I Made (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The occurrence of sexual harassment by a religious figure was addressed in a decision by the Denpasar District Court, Decision Number 266/Pid.B/2021/PN Dps,, concerning this case. In the decision, it was stated that an individual named IWM (initials used by the writer) was legally and convincingly proven to have committed an act of obscene behavior with violence as defined in Article 289 of the Indonesian Criminal Code (KUHP). Therefore, stricter enforcement by the traditional village through the implementation of more stringent customary sansctions is necessary. Based on this explanation, the aim of this research are: 1. To analyze the urgency of the need for the concept of customary sanctions for cases of sexual harassment by religious figures in Tampaksiring Village, Tampaksiring District, Gianyar Regency. 2. To analyze the form of the concept of customary sansctions for cases of sexual harassment by religious figures in Tampaksiring Village, Gianyar Regency. This study utilizes empirical legal research, employing the theory of law known as the theory of receptie. The findings of the study indicate the form of customary sansctions is regulated in the awig-awig (customary law) Saptamas Sargah Wicara Lan Pamidanda Palet 2 Indik Pamidanda Pawos 75. The sanctions applied for sexual harassment include Penyangaskara punishment which entails conducting religious ceremonies, requiring the offering of banten pecaruan to restore magical balance. In addition to Penyangaskara sanctions, it is also conceptualized that customary sanctions include menyaksama or mapilaku (asking for forgiveness) in front of the village's paruman (traditional village council). As an effort by the traditional village to tackle sexual harassment, one measure is to tighten the reporting of visitors if they come to a sacred place.